THU0630-HPR Validation of the Activpal™ Activity Monitor for Sedentary and Physical Activity Patterns in People with Rheumatoid Arthritis. (9th June 2015) - Larkin, L.; Nordgren, B.; Brand, C.; Fraser, A.; Kennedy, N.
Abstract : Background: Accurate measurement of physical activity and sedentary behavior is an important consideration for healthcare professionals (1). Two objective measures of physical activity have been validated in people who have rheumatoid arthritis (RA) (2, 3). However no objective measure has been validated to measure sedentary behavior in people who have RA to date. The ActivPAL™ activity monitor can measure both physical activity and sedentary behavior but has not been validated in people who have RA. Objectives: The aim of this study was to determine the validity of the ActivPAL™ activity monitor in measuring time spent in sedentary, standing/light activity, and walking behaviors as well as step count and transition count. Methods: Participants with a confirmed medical diagnosis of RA were recruited from two outpatient rheumatology clinics. Testing protocol consisted of a controlled section and activities of daily living section. Participants wore one ActivPAL™ activity monitor on each thigh and were video recorded throughout the testing procedure. Direct observation was used as the criterion measure. Statistical analysis consisted of (i) inter-rater and inter-device reliability (intraclass correlation) (ICC) and (ii) validation analysis of ActivPAL™ activity monitor data and the criterion measure data (ICC and Bland and Altman analysis). Results: Twenty-four participants participated in the study, with data from twenty participants being included in the final analysis. The ActivPAL™ activity monitor accurately measured time spent in sedentary (ICC=0.516, limits of agreement -298.7 to 321.6), standing/light activity (ICC=0.732, limits of agreement -174.3 to 267.1) and walking (ICC=0.839, limits of agreement -72.4 to 53.3) behaviors only. The ActivPAL™ underestimated step count by 27% (ICC=0.630, limits of agreement -235.4 to -18.8) and transition count by 36% (ICC=-0.013, limits of agreement -7.9 to 0.0) in our sample population. Conclusions: The ActivPAL™ activity monitor is a valid measure of time spent in sedentary, standing/light activity and walking behaviors when compared to direct observation in people who have RA. It underestimated step and transition count in our study and thus is not valid for measuring these outcomes in people who have RA. References: Warren, MJ, Ekelund, U, Besson, H, Mezzani, A, Geladas, N, Vanhees, L. (2010). Assessment of physical activity - a review of methodologies with reference to epidemiological research: a report of the exercise physiology section of the European Association of Cardiovascular Prevention and Rehabilitation. European J of Cardiovasc Prev and Rehabil 17(2):127-39 Tierney M, Fraser A, Purtill H, Kennedy N. (2013).Study to determine the criterion validity of the SenseWear Armband as a measure of physical activity in people with rheumatoid arthritis. Arthritis Care Res 65:888-95 Munneke M, de Jong Z, Zwinderman AH, Tijhuis GJ, Hazes JM, Vliet Vlieland TP. (2001). The value of a continuous ambulatory activity monitor to quantify the amount and intensity of daily activity in patients with rheumatoid arthritis. J Rheumatol 28:745–50 Disclosure of Interest: None declared